The Effect of Oxytocin Massage on Postpartum Mother Breast Milk Production at Pejeruk Public Health in the Year of 2017 - Pilaria, Ema (Lembaga Penelitian Universitas YARSI, 2018)
Background: Basic Health Research (2013) data shows that the scope of exclusive Breastfeeding in Indonesia is only 42%. In Mataram City (2015) the percentage of exclusive breastfeeding is only 62.35%. Meanwhile, the target of exklusive breastfeeding in Indonesia has to reach 80%. One of the low exclusive breastfeeding causes is less amount of breast milk production in the first day after giving a birth which is caused by less oxcytocin and prolactin hormones stimulation in which they have a role to smoothen breast milk production that causes breast milk couldn’t immediately out after giving a birth. The nonfarmakologis effort, oxytocin massage is required to make the breast milk out.Objective: To know Effect of Oxytocin Massage on Postpartum Mother Breast Milk Production at Pejeruk Public Health in the Year of 2017.Method: This research used quasi experiment method with one group pre and post test design (measurement of research before and after intervention). The Measurement used observation sheet (breast milk production) thereafter intervention (oxytocin massage) was given which followed by the 3rd day evaluation using the observation sheet (breast milk production). The intervention result was compared with the result of measurement before the intervention given.Result: Characteristics of thee majority oxytocin massagen respondents based on the age 20-35 is 22 respondens (73,3%), paritas multipara 21 respondents (70%) and normal lila 23,5-26,5 cm is 15 respondents (50%). The production of breast milk before oxytocin massage 15 mostly not enough 24 respondents (80%), after given oxytocin massage the production of breast milk is enough from 27 respondents (90%). Statistical test result using Mcnemar Test obtained p value = 0.000 or p <α = 0,05.Conclusion: There is an effect of oxytocin massage on postpartum mother breast milk production at Pejeruk Public Healt in the Year of 2017.